Outcomes of a mentoring scheme to improve career engagement in academia among students from minority ethnic groups - Nwosu, Chiamaka (Frontiers in Education, 2024)
IntroductionStudent mentorship in higher education institutions is often advocated as a way to improve opportunities for students from minority ethnic groups.MethodsThis study examines this further by applying a linear regression model to explore the relationship between a 6-month pilot mentoring scheme at King's College London and career engagement in academia for students from minority ethnic groups, by investigating whether there were differential impacts by ethnic group, and by degree of exposure to mentoring, measured by the number and mode of mentoring sessions i.e., online, in-person or bimodal (a combination of online and in-person).ResultsThe results reveal that while there were no significant differences in career engagement between Asian and Black students, there were significant differences in career engagement between Black students and students who identified as Mixed or Other. Surprisingly, the number of sessions was negatively related to career engagement. However, the positive, significant interaction effect between the number and mode of sessions suggests that this relationship varies based on the mode of the sessions, with bimodal sessions leading to an increase in career engagement, in contrast to solely in-person sessions which led to a decrease in career engagement in academia.ConclusionThe results from this study point to some differential effects of mentoring by ethnic group, with Black students experiencing less gains in terms of career engagement in academia, relative to students who identified as Mixed or Other ethnic groups. This suggests that Black students may need more tailored support, in-depth mentoring or better-matched role models for improved outcomes.